Effect of Incubation Time on Amylase Enzyme Activity in Sticky Rice Tape (International Journal of Ecophysiology, 2022)
Indonesia uses fermentation as a common method of food processing. Tape ketan is one of the foods produced using the fermentation process. The enzyme amylase, which hydrolyzes carbohydrates (starch) into sugar, is involved in the fermentation process of sticky rice tape. Many factors affect the activity of the amylase enzyme. Incubation time is one of them. The length of incubation can also impact the tape's sweetness, color, texture, and scent. The 48- hour incubation period had the maximum amylase activity. Organoleptic testing, meanwhile, revealed a range of color, scent, texture, and taste. We'll talk about how the amylase enzyme's activity and incubation period relate to the color, flavor, texture, and aroma of sticky rice tape in this article